(3TQM OjhGf TYQ GdMGOQIs - (3dCHi YHO Gddg eMeO Hf GdYHGS Hf eMeO GdjRjOis; (3GdMGOQI , bWHI Hf GhS Hf eMUf Hf LQhd GdeGRfj GdZWaGfj, GdMGOQgs ((3YHO Gddg s)
(3ChdgG (B:s
(3cCfc MGOQI GdefcHjf QUYGA JfbV ai MGFQ s
(3BNQgG (B:s
(3bGd CHh YHO Gddg GdjRjOi Yf GHf YQGHi bGd SeYJ CYQGHjkG jbhd hGf TQ GdZHjGJ ZHjI GdfHdJe TYQ GdMGOQI HMeO Gddg s
(3JJab ai ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGX HgG fbU OGNdgG hGVWQGH ai JQJjH HYV ChQGbgGs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs